Program Evaluation of the Strength Conditioning Team in Improving the Physical Condition of Men Futsal Athletes in Tangerang Regency for PORPROV V Banten 2018 - Muhamad Rizki Febrian Putra; Gustiana Mega Anggita (Gladi : Jurnal Ilmu Keolahragaan, 2022)
Good physical condition is needed by athletes in any kind of sport, particularly in futsal. This type of research is descriptive qualitative research model that uses the CIPP evaluation model (Context, Input, Process, and Procuct). This research use observation, interview and documentation to collect data. The population for this research consists of athletes, choaches, AFKAB administrators, and Tangerang official KONI administrators. To verify the validity of the data, this research use triagulation of sources. The data analysis techniques used to analyze this research are data collection, data reduction, data presentation, and drawing conclusions. Rwaukt : Context, the main purpose of the futsal’s strenght and conditioning team program are in line with the KONI Tangerang main goals. Input, human resources of futsal’s strenght and conditioning tam program are already compatible with the qualifications that has been defined at the begining, however the facilites that supose to help improve the physical codition of futsal athletes are inadaquate. Process, team streght conditioning provide training material base on the training program structure that has been arranged before, team strenght conditioning also evaluates the training material regularly by recording the development of the athletes physical condition. Product, the final physical test result obtained that 62% of the physical condition of male futsal atheles from Tangerang regency reached the physical trainer's target of aerobic endurance (VO2 Max) and the achievement of the male futsal athletes of Tangerang Regency increased. The conclusion of this study is that the strength conditioning team program has full fill the goal, and in line with the needs of futsal athletes, although there are still inadequate factors, KONI Tangerang Regency continues to make maximum efforts. Keywords: Evaluation Program, CIPP, Strength Conditioning Team, Condition Physical